AHEDO, J., FUENTES, J. L. y CARO, C. (Coords.). (2020). Educar el carácter de nuestros estudiantes. Reflexiones y propuestas para la escuela actual. Madrid: Narcea, 168 paginas, ISBN 978-84-277-2774-8 - Mª Luisa Barceló Cerdá (Universidad de La Rioja, 2021)
AHEDO, J., FUENTES, J. L. y CARO, C. (Coords.). (2020). Educar el carácter de nuestros estudiantes. Reflexiones y propuestas para la escuela actual. Madrid: Narcea, 168 paginas, ISBN 978-84-277-2774-8.